The Contribution of English Proficiency to the Development of Soft Skills in Tourism Students - Hanan, Ahmad; Tawali, Tawali (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study examines the role of English language proficiency in developing students' soft skills in students enrolled in tourism study programs. Using a descriptive quantitative design with correlational design, the data were collected from 100 students enrolled in tourism courses using a structured questionnaire. The research indicated a moderate positive correlation between English competence and students' soft skills, including communication, teamwork, and intercultural competence. The strongest correlation was between English competence and communication competence, highlighting the facilitating function of English as a medium for enhanced professional communication in the context of tourism. The study opines that learning English language as part of tourism education should not only focus on linguistic ability but also the acquisition of soft skills to make the students more employable. It provides suggestions for teachers, curriculum designers, and future researchers to integrate English education with soft skill training through communicative and experiential learning approaches.